Synthesis of sulfadimethoxine based surfactants and their evaluation as antitumor agents - Khowdiary, Manal; Mostafa, Nashwa (Journal of cancer research and therapeutics, 2016)
Aim of the Study: Synthesized CO (II) and Pt (II) of sulfadimethoxine. These compounds were tested for potential antitumor activity against two of human tumor cell lines, colon carcinoma cell line [Hct116], and breast carcinoma cell line MCF7. Materials and Methods: The structures of the resulting compounds have been investigated by elemental, FT-IR and H 1 NMR analyzes to insure the purity and confirmed the structures of them. The surface properties studies and octanol/water partition coefficients, Po/w were measured. Results: The synthesized compounds exhibit biological activities with the lowest log Po/w and critical micelle concentration (CMC) values. In addition, in this article we provide an insight into this subject in order to increase the drug bioavailability. Inhibitory activity against colon carcinoma cells was detected for Pt and cobalt ion complex with IC50 = 4.5, 2.2 µg and against breast carcinoma cells IC50 = 18.2, 5.7 µg, respectively. Summary: The main goal of cancer therapy is to attain the maximum therapeutic damage of tumor cells in combination with a minimum concentration of the drug. This can be achieved in principle via selective antitumor preparations, the cytostatic effects of which would be restricted within tumor tissue. While 100% selectivity may be impractical, the achievement of reasonably high selectivity seems to be a feasible aim. Platinum and cobalt complex surfactants in our research affect tumor tissue at a very low concentration at values lower than their CMC values; this indicate that the sulfadimethoxine complexes merit further investigation as potential antitumor drugs.